(untitled) (Revista Puertorriqueña de Psicologia, 2018)
The 4th CRCP will be held in November in Jamaica. Please join CANPA National member organizations and Caribbean colleagues for a week of discussion, conviviality, and learning! Theme: Transforming Psychology" Embracing Caribbean Realities Sub-Themes -Promoting Caribbean Health and Well-being -Multiculturalism / Multilingualism in the Caribbean -Caribbean Psychology Education and Training -Caribbean Psychology in Applied Settings -Challenges in Psychology For inscriptions and more information, please visit: http://www.crcp2018.org/